Pengembangan Tata Letak Bengkel dan Program Praktik Fabrikasi Logam di SMK N 1 Seyegan - Aris Sulistyo; Putut Hargiyarto (Jurnal Dinamika Vokasional Teknik Mesin, 2019)
The purpose of this research and development are to plan a workshop layout, a program for practical works and to identify the inhibiting and supporting factors in the implementation stage. The development model used uses Analysis, Design, Implementation, and Evaluation. The subject of the research and development are teachers and technicians working in Metal Fabrication Workshops.  The data were collected using observation, interviews, and documentation. The results of the study are metal fabrication workshop layouts, practical work program, and identification of the inhibiting and supporting factors in the research and development.Tujuan penelitian dan pengembangan ini adalah menghasilkan layout bengkel, program praktik dan identifikasi faktor penghambat, pendukung. Model pengembangan menggunakan Analisis, Desain, Implementasi dan Evaluasi. Subjek pada penelitian dan pengembangan ini adalah Guru dan Teknisi Bengkel Teknik Fabrikasi Logam. Alat pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Hasil berupa layout bengkel praktik fabrikasi logam, komponen program praktik dan identifikasi faktor pendukung, penghambat dalam penelitian dan pengembangan